Employee Loyalty And Engagement Mediating The Impact Of Transformational Leadership On Employee Performance - Rochim, Achmad; Fauzi, Akhmad; Rini, Hesty Prima (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
In the construction industry, transformational leadership, employee engagement, and loyalty are important factors in individual change and development within an organisation, which determine work effectiveness and productivity, as well as employee performance. The purpose of this study is to analyse (1) the influence of transformational leadership on employee performance, (2) employee loyalty mediating the influence of transformational leadership on employee performance, and (3) employee engagement mediating the influence of transformational leadership on employee performance. The sample of this study consists of field technicians at PT. Panca Indah Jayamahe, totaling 105 respondents. The sampling technique used is saturated sampling (census). The primary data used was collected through a questionnaire distribution to respondents. The analysis is conducted using the Structural Equation Model - Partial Least Square (SEM-PLS) method with Smart PLS version 4.0 software. The study results conclude that (1) transformational leadership has a significant positive effect on employee performance, (2) employee loyalty mediates the influence of transformational leadership on employee performance, and (3) employee engagement mediates the influence of transformational leadership on employee performance